Design and Manufacture of Wireless Monitoring system of Photovoltaic Generation Employing Raspberry PI 3 - Krismadinata, Krismadinata; Kusuma, Puja; Yahfizham, Yahfizham (ELKHA : Jurnal Teknik Elektro, 2021)
This paper recounts design and development the realtime and wireless monitoring systems to observed the characteristics and performanced of the solar photovoltaic (pv) energy generation. The monitoring systems designed used the Raspberry Pi 3 as the data processing center, the voltage divider as the voltage sensor, ACS712 as the current sensor, DHT as the temperature sensor, and BH1750 as the solar irradiation sensor. The measurements of the pv generation characteristics are carried out all the time in real time. The monitoring systems developed has calibrated with standard measuring instruments. The measurement data has processed, sent and stored in the database via the internet. The MySQL database with single user interface using the Web-based programming language has employed. This research has proven that the system designed to functioning properly and correctly to achieve the objectived. The novelty of these project are the pv wireless monitoring systems techniques with the simple device resources, capable of showing maximum performanced.